2020
DOI: 10.1016/j.scitotenv.2020.138234
|View full text |Cite
|
Sign up to set email alerts
|

Environmental health conditions in protracted displacement: A systematic scoping review

Abstract: Adequate environmental health services are critical for human rights, health, and development, especially in the context of forced displacement. There are more than 70 million forcibly displaced persons worldwide, most in protracted situations, having been displaced for more than two years. Some live in camps or informal settlements, but most live in urban areas. Environmental health services are important in the transition from emergency response to sustainable development in these settings, but evidence on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Several studies have reported the presence of SARS-CoV-2 in feces and wastewater (Holshue et al, 2020;Wang et al, 2020a;Annalaura et al, 2020). Leakage of sewerage system when conveying wastewater containing contaminated excretes is one of the ways by which sanitary related diseases can be contracted by human beings (Behnke et al, 2020;Gormley et al, 2020). The best way to address this is to create a decentralized wastewater treatment facility.…”
Section: Decentralization Of Wastewater Treatment Facilitiesmentioning
confidence: 99%
“…Several studies have reported the presence of SARS-CoV-2 in feces and wastewater (Holshue et al, 2020;Wang et al, 2020a;Annalaura et al, 2020). Leakage of sewerage system when conveying wastewater containing contaminated excretes is one of the ways by which sanitary related diseases can be contracted by human beings (Behnke et al, 2020;Gormley et al, 2020). The best way to address this is to create a decentralized wastewater treatment facility.…”
Section: Decentralization Of Wastewater Treatment Facilitiesmentioning
confidence: 99%
“…Studies from both peer-reviewed and grey literature sources were searched using the strategy described by Behnke et al (2020). Peer-reviewed studies were identified through the…”
Section: -Search Strategymentioning
confidence: 99%
“…Settlements for displaced populations are primarily designed to provide rapid onset emergency support, such as basic shelter, medical care, nutrition, and water, sanitation and hygiene (WaSH) facilities. However, they often fail to meet minimum environmental health standards, and are ill-suited to longer-term displacement (Behnke et al, 2020;Cronin et al, 2008;Sphere Association, 2018;van der Helm et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several works have implied from various perspectives the rise of environmental health. Behnke et al (2020) conducted a systematic scoping review of environmental conditions, exposures, and outcomes in protracted displacement settings, obstacles to improvement in environmental health services. The data were extracted on environmental health topics, including water, sanitation, hygiene, overcrowding, waste management, energy supply, vector control, menstrual hygiene, air quality, and food safety.…”
Section: Second Stage: Covid-19 and Sustainability Conceptual Modelsmentioning
confidence: 99%